Maran entre Chateaubriand et Rabearivelo - Jean-Louis Cornille (Études Caribéennes)
After having shown how much Batouala remains indebted to the great romantic classics (mainly Chateaubriand) in its formatted description of nature (or eco-text), we’ll analyse how in 1926 a young Malagasy poet, Jean-Joseph Rabearivelo, subscribes to the same literary vain by following in René Maran’s footsteps. Furthermore, we’ll show how Rabearivelo multiplies the textual echoes to Batouala at a cultural level as well, in his effort to write a truly malagasy novel.